2014
DOI: 10.4236/jwarp.2014.614121
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Simulation in a Data-Scarce Basin Using Reanalysis and Global Precipitation Data: A Case Study of the White Volta Basin

Abstract: Basins in many parts of the world are ungauged or poorly gauged, and in some cases existing measurement networks are declining. The purpose of this study was to examine the utility of reanalysis and global precipitation datasets in the river discharge simulation for a data-scarce basin. The White Volta basin of Ghana which is one of international rivers was selected as a study basin. NCEP1, NCEP2, ERA-Interim, and GPCP datasets were compared with corresponding observed precipitation data. Annual variations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The estimation of available water resources using hydrologic modeling provides important information for planners and policy makers to mitigate problems arising due to water shortages. The subject of performing hydrologic predictions in sparsely gauged West African river basins has been well covered in recent years [4][5][6][7][8][9][10][11]. Due to a continuous decline in ground-based observation networks as a consequence of political unrest and financial instability [12,13], the authors explored the possibility of setting up the semi-distributed Soil and Water Assessment Tool (SWAT) model [14][15][16] for several West African river basins in a previous study [11].…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of available water resources using hydrologic modeling provides important information for planners and policy makers to mitigate problems arising due to water shortages. The subject of performing hydrologic predictions in sparsely gauged West African river basins has been well covered in recent years [4][5][6][7][8][9][10][11]. Due to a continuous decline in ground-based observation networks as a consequence of political unrest and financial instability [12,13], the authors explored the possibility of setting up the semi-distributed Soil and Water Assessment Tool (SWAT) model [14][15][16] for several West African river basins in a previous study [11].…”
Section: Introductionmentioning
confidence: 99%
“…The area of the Sampean Baru, Bedadung, and Mayang watersheds are approximately 703 km 2 , 648 km 2 , and 578 km 2 , respectively, taken from the Digital Elevation Model (DEM) with a resolution of 30x30m. The number of meteorological stations and the drainage patterns of the Sampean Baru (22), Bedadung (14), and Mayang (11) watersheds is depicted in Figure 1. The density of the rain station network per km 2 from densest to sparse for the Sampean Baru, Bedadung, and Mayang watersheds overall respectively were 31.96, 46.46, and 52.6.…”
Section: Study Area Descriptionmentioning
confidence: 99%
“…Spatial scarcity of rain gauge networks or none at all, especially upstream due to the difficulty of reaching them, poses a challenge to the accuracy of hydrological models Behrangi et al, 2011;Bitew & Gebremichael, 2011; Koutsouris et al, 2016). The availabhility of freely available satellite-based rainfall products with high spatial and temporal resolution can solve the challenge or even replace the measurement of rain gauges (Fujihara et al, 2014;Koutsouris et al, 2016;Thiemig et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, the lack of global and sufficiently dense precipitation references makes these results of satellite-based precipitation still unreliable and inadequate for operational purposes, such as flood forecasting [35]. Therefore, a regional ground validation of satellite-based precipitation datasets based on dense gauges references, especially for their hydrological performances, still requires to be conducted [36][37][38][39][40][41][42][43][44]. Although most studies revealed the potential of satellite-based precipitation datasets for hydrological simulations, they also report error sources during the hydrological modeling of satellite-based datasets.…”
Section: Introductionmentioning
confidence: 99%